Pelatihan Penyusunan Program Layanan Bimbingan dan Konseling Untuk Meningkatkan Kompetensi Bagi Guru Bimbingan dan Konseling di SMP - Muhammad Fauzi Hasibuan; Jamila Jamila; Ismail Saleh Nasution (CERED Indonesia Publishing, 2020)
Planning and preparation of guidance and counseling programs is an important step in the development of guidance. The goal is for all activities to be organized and systematically coordinated, so that they can run smoothly, efficiently, effectively towards achieving a goal. Guru BK's main tasks are to develop guidance programs, implement guidance programs, evaluate guidance programs, analyze the results of guidance implementation and follow-up in guidance programs for students whose responsibilities are the responsibility. The Guidance and Counseling Program is only described according to the types of services and areas of development without any description of the allocation of time, the classes that will be provided the service, the materials that will be presented and the absence of weekly programs. In other words, the preparation of guidance and counseling programs has not been in accordance with the guidelines for the preparation of guidance and counseling programs.The purpose of training in the preparation of guidance and counseling services program for BK teachers is to provide understanding and insight to develop and develop guidance and counseling programs ideally and professionally, so as to provide good implementation for students. The results of this community service activity show that training in the preparation of guidance and counseling services programs to junior high school teachers: First, there is an increased understanding of teachers towards the preparation of guidance and counseling services programs in the form of. Second, obtained the results of draft guidance and counseling services programs that can be developed by teachers.